America's history - Henretta, James A.; Edwards, Rebecca; Self, Robert O. (Bedford/St. Martins, 2011)
Part 1 : The creation of American society, 1450-1763. The new global world -- The invasion and settlement of North America -- Creating a British Empire in America -- Growth and crisis in colonial society -- Part 2 : The new republic, 1763-1820. Toward independence : years of decision -- Making war and republican governments -- Politics and society in the new republic -- Creating a republican culture -- Part 3 : Overlapping revolutions, 1820-1860. Economic transformation-- A democratic revolution -- Religion and reform -- The South expands : slavery and society -- Part 4 : Creating and preserving a continental nation, 1844-1877. Expansion, war, and sectional crisis -- Two societies at war -- Reconstruction -- Conquering a continent -- Part 5 : Bold experiments in an era of industrialization, 1877-1929. The busy hive : industrial America at work -- The Victorians meet the modern -- Civilization's inferno : the rise and reform of industrial cities -- Whose government? : Politics, populists, and progressives -- An emerging world power -- Wrestling with modernity -- Part 6 : The modern state and the age of liberalism, 1929-1973. The Great Depression and the New Deal -- The world at war -- Cold War America -- Triumph of the middle class -- Walking into Freedom Land : the civil rights movement -- Uncivil wars : liberal crisis and conservative rebirth -- Part 7 : Global capitalism and the end of the American century, 1973-2011. The search for order in an era of limits -- Conservative America ascendant -- National dilemmas in a global society -- Documents -- Appendix -- Glossary.